Separation and Characterization of Antioxidative and Angiotensin Converting Enzyme Inhibitory Peptide from Jellyfish Gonad Hydrolysate - Zhang, Qin; Song, Chengcheng; Zhao, Jun; Shi, Xiaomei; Sun, Meiling; Liu, Jing; Fu, Yinghuan; Jin, Wengang; Zhu, Beiwei (Molecules (Basel, Switzerland), 2018)
The gonad of jellyfish (Rhopilema esculentum Kishinouye), containing high protein content with a rich amino acid composition, is suitable for the preparation of bioactive peptides. Jellyfish gonad was hydrolysed with neutral protease to obtain jellyfish gonad protein hydrolysate (JGPH), which was then purified sequentially by ultrafiltration, gel filtration chromatography, and RP-HPLC. The peptides were characterized with HPLC-MS/MS. One peptide with amino acid sequence Ser-Tyr (SY) was identified and synthesized, which showed good ACE inhibitory and antioxidant activity. The IC50 of this peptide on DPPH, ·OH, super oxygen anion scavenging activities, and ACE inhibitory activity are 84.623 μM, 1177.632 μM, 456.663 μM, and 1164.179 μM, respectively. The anchor in the binding site of SY and ACE C-domain (ACE-C) was obtained by molecular simulations. The results showed that the dipeptide purified from jellyfish gonad protein hydrolysates can be used as functional food material and is helpful in the study of antioxidant and inhibition of ACE.